Strategi peningkatan kualitas layanan perpustakaan institut bakti nusantara berperspektif servqual - Nazwa Rifani; Eni Amaliah; Rahmat Iqbal (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2026)
Background of the Study: Library service quality plays an important role in supporting user satisfaction and optimizing access to information resources. However, several aspects of library services at Institut Bakti Nusantara (IBN) Pringsewu still require improvement, particularly in facilities, service systems, and human resources. Objectives: This study aims to analyze the quality of library services at the Library of Institut Bakti Nusantara (IBN) Pringsewu based on the five SERVQUAL dimensions (tangibles, reliability, responsiveness, assurance, and empathy) and to formulate strategies for improving library services. Method: This study employed a descriptive qualitative approach. Data were collected through interviews, observations, and documentation involving librarians and library users. The data were analyzed descriptively using the five SERVQUAL dimensions: tangibles, reliability, responsiveness, assurance, and empathy. Finding: The results show that the tangibles, reliability, and responsiveness dimensions have not been fully optimized due to limitations in facilities, collection updates, system stability, and human resources. Meanwhile, the assurance and empathy dimensions were implemented well through professional services, courteous staff attitudes, and user-oriented assistance in library collection management. Conclusion: Improving library service quality requires enhancing library facilities and collections, increasing system reliability, strengthening human resources, maintaining professional service standards, and sustaining user-oriented practices to improve overall library service quality.